NR4A1 modulates intestinal smooth muscle cell phenotype and dampens inflammation‐associated intestinal remodeling. Issue 11 (17th October 2022) - Szczepanski, Holly E.; Flannigan, Kyle L.; Mainoli, Barbara; Alston, Laurie; Baruta, Grace M.; Lee, Joshua W.; Venu, Vivek Krishna Pulakazhi; Shearer, Jane; Dufour, Antoine; Hirota, Simon A.
Abstract: Stricture formation is a common complication of Crohn's disease (CD), driven by enhanced deposition of extracellular matrix (ECM) and expansion of the intestinal smooth muscle layers. Nuclear receptor subfamily 4 group A member 1 (NR4A1) is an orphan nuclear receptor that exhibits anti‐proliferative effects in smooth muscle cells (SMCs). We hypothesized that NR4A1 regulates intestinal SMC proliferation and muscle thickening in the context of inflammation. Intestinal SMCs isolated from Nr4a1 +/+ and Nr4a1 −/− littermates were subjected to shotgun proteomic analysis, proliferation, and bioenergetic assays. Proliferation was assessed in the presence and absence of NR4A1 agonists, cytosporone‐B (Csn‐B) and 6‐mercaptopurine (6‐MP). In vivo, we compared colonic smooth muscle thickening in Nr4a1 +/+ and Nr4a1 −/− mice using the chronic dextran sulfate sodium (DSS) model of colitis. Second, SAMP1/YitFc mice (a model of spontaneous ileitis) were treated with Csn‐B and small intestinal smooth muscle thickening was assessed. SMCs isolated from Nr4a1 −/− mice exhibited increased abundance of proteins related to cell proliferation, metabolism, and ECM production, whereas Nr4a1 +/+ SMCs highly expressed proteins related to the regulation of the actin cytoskeleton and contractile processes. SMCs isolated from Nr4a1 −/− mice exhibited increased proliferation and alterations in cellular metabolism, whereas activation of NR4A1 attenuated proliferation. In vivo, Nr4a1 −/− mice exhibited increased colonic smooth muscle thickness following repeated cycles of DSS. Activating NR4A1 with Csn‐B, in the context of established inflammation, reduced ileal smooth muscle thickening in SAMP1/YitFc mice. Targeting NR4A1 may provide a novel approach to regulate intestinal SMC phenotype, limiting excessive proliferation that contributes to stricture development in CD.